2018
DOI: 10.1017/s0960258518000314
|View full text |Cite
|
Sign up to set email alerts
|

Seed traits and germination of native grasses and invasive forbs are largely insensitive to parental temperature and CO2concentration

Abstract: The structure and function of grassland ecosystems can be altered by a changing climate, including higher temperature and elevated atmospheric CO2 concentration. Previous studies suggest that there is no consistent trend in seed germination and seedling recruitment as affected by these conditions. We collected seeds of two native and two invasive species over 6 years from a field study with elevated CO2 (600 p.p.m.) and temperature (1.5/3.0°C day/night) on the mixed-grass prairie of Wyoming, USA. Seed fill, vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Since climate warming can influence plant invasions (Bradley et al, 2010), this has particular relevance to seed quality and seed germination (Aragn-Gastlum et al, 2018). For example, recent studies have shown that climate warming may strongly influence seed quality and seed germination (Aragn-Gastlum et al, 2018;Li et al, 2018) and plant mortality and phenology during the invasion process (Peng et al, 2018;He and He, 2020). Plant populations from native and non-native ranges perform differentially, including reproductive output, seedling recruitment, individual density, and competitive ability (Lockwood et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Since climate warming can influence plant invasions (Bradley et al, 2010), this has particular relevance to seed quality and seed germination (Aragn-Gastlum et al, 2018). For example, recent studies have shown that climate warming may strongly influence seed quality and seed germination (Aragn-Gastlum et al, 2018;Li et al, 2018) and plant mortality and phenology during the invasion process (Peng et al, 2018;He and He, 2020). Plant populations from native and non-native ranges perform differentially, including reproductive output, seedling recruitment, individual density, and competitive ability (Lockwood et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, when the first Therefore, the interaction between temperature and CO 2 did not have a significant effect on the final emergence of either species of Capsicum evaluated. In contrast, a significant increase in the percentage of emergence was observed in Bouteloua gracilis with the combination of seven temperatures with alternating 12/12 h periods (10/0, 12.5/2.5, 15/5, 20/10, 25/15, 30/20, 35/25 • C) and CO 2 (385 and 600 µmol CO 2 mol −1 ) [18]. Moreover, [25] mention that CO 2 concentration did not have a significant effect on Arabidopsis thaliana seed emergence, with seeds subjected to high temperatures exhibiting the fastest germination rate.…”
Section: Seedling Emergencementioning
confidence: 80%
“…The physiological response of seeds to this factor is crucial for emergence and plant development, and once the optimum temperature point is reached, the emergence process diminishes. Therefore, temperatures under or over the maximum optimum can inhibit emergence, risking the life and survival of seedlings [18,27,28].…”
Section: Seedling Emergencementioning
confidence: 99%
See 1 more Smart Citation